SISTEM INFORMASI GEOGRAFIS PENCARIAN LOKASI WISATA TERDEKAT DI KABUPATEN JEPARA MENGGUNAKAN METODE HILL CLIMBING (Science and Technology (SciTech), 2023)
Jepara is one of the regencies in Central Java which is quite potential in the tourism sector. There are natural attractions, artificial tours, and cultural tourism. For tourists from outside Jepara, people find it difficult to determine the location choices they want to visit. To overcome this problem, a Geographic Information System was created, combined with the Hill Climbing method. Hill Climbing is a method that uses heuristic functions in the testing process. All possible solutions will be checked one by one from the far left side, so the optimal results can be obtained. Thus, tourists will find recommendations for several choices of nearby tourist sites in Jepara.